1994
DOI: 10.1007/bf01259562
|View full text |Cite
|
Sign up to set email alerts
|

Data quality of bedside monitoring in an intensive care unit

Abstract: Computerized record keeping promises complete, accurate and legible documentation. Reliable measurements are a prerequisite to fulfill these expectations. We analyzed the physiological variables provided by bedside monitoring devices in 657 bedside visits performed by an experienced Intensive Care nurse during 75 Intensive Care rounds. We registered which variables were displayed. If a variable was displayed, we assessed whether it could be used for documentation or should be rejected. If a value was rejected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…Therefore the quality of automatically recorded and stored data points (actual values or means) remains questionnable. Friesdorf et al showed that less than 85 % of invasively measured blood pressure values were reliable at the time of assessment, similar results were seen for other 157 monitoring data [28]. Thus, in our experience, data recorded without validation can (at present) hardly be used for automated calculations (e.g.…”
Section: Database Quality and Critical Care Researchsupporting
confidence: 84%
“…Therefore the quality of automatically recorded and stored data points (actual values or means) remains questionnable. Friesdorf et al showed that less than 85 % of invasively measured blood pressure values were reliable at the time of assessment, similar results were seen for other 157 monitoring data [28]. Thus, in our experience, data recorded without validation can (at present) hardly be used for automated calculations (e.g.…”
Section: Database Quality and Critical Care Researchsupporting
confidence: 84%
“…This was consistent with prior reports that unreliable vital sign data are all too typical in clinical practice [1,2,[4][5][6]. To deal with missing data, we used an ensemble classifier for multivariate classification, which was significantly better than univariate classification.…”
Section: Specific Findingsmentioning
confidence: 51%
“…In terms of the external validity of the study, the issues that we studied have been previously recognized [1,2,[4][5][6]. This report offers a novel, quantitative analysis of their magnitude of effect in actual prehospital practice.…”
Section: Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Continual physiologic monitoring, e.g., within the Intensive Care Unit (ICU), poses a work burden on caregivers who must regularly document the data. Although recent computing capabilities make it technologically feasible to automatically record voluminous, continuous physiologic data, it may not be desirable: automatically archived data may be overly polluted with the measurement errors and artifacts that are known to corrupt physiologic data [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%